Review on Acute Cardio-Cerebral Infarction: a Case Report - Teddy Arnold Sihite; Michi Astuti Rehmenda Mario Sitepu; Cut Azlina Effendi (International Journal of Integrated Health Sciences, 2021)
Objective: To describe a case of a Cardio-Cerebral Infarction (CCI) male patient presented with a history of chest pain recognized using electrocardiography, brain computed tomography, and Percutaneous Coronary Intervention (PCI).